The conception of archive in society of the information: PARES like motor of change - Ruiz Astiz, Javier (Revista General de Información y Documentación, 2013)
PARES act as if it was a unique virtual file that it tries to serve as referring for the diffusion of our culture. The present article tries to analyze the new conception of the file in the society of the information. First the important thing will be verified that it is to come to the digitalization of documents to try to conserve them and to spread them. Later mention to the interest will be made that wakes up our culture through study of the technologies of the information and communication. Thirdly we will deepen in the option that supposes for us the diffusion of the documentary patrimony. And finally, all this will be argued on the basis of the data that to us the use of the platform in the years throws that takes in operation, verifying itself its full success.
Keywords: Digital archive; PARES; Access; Culture; User.